On the presence of an unexpected meadow of Penicillus capitatus Lamarck (Bryopsidales: Chlorophyta) in Mallorca, Balearic Islands, Western Mediterranean - HIERRO, ANDREA; BALLESTEROS, ENRIC; MAÑEZ-CRESPO, JULIA; REYNÉS, XESCA; TOMAS, FIONA (Mediterranean Marine Science, 2024)
An unexpected meadow of the warm-water alga Penicillus capitatus was found thriving in sandy bottoms between 16 and 21 m depth in Mallorca, Balearic Islands. Plant densities and benthic coverage were very high when compared to most Mediterranean meadows of this species. As it is common in tropical meadows of this species, all the individuals were found in a Penicillus morphological state, whereas most Mediterranean individuals are always found in the filamentous (Espera) state. Due to the high biomass of the populations, the contribution to the primary productivity of the sandy bottoms it colonizes should be far from negligible. If the expansion of these species continues, the annual calcium carbonate production of the Balearic continental shelf will increase and previous estimated budgets will have to be reconsidered. Since no genetic analysis of the specimens have been performed so far, it is still early to know if the studied populations have been originated by native Mediterranean specimens or from a cryptic lineage of Western Atlantic or Macaronesian origin. Whatever the answer is, the current bloom of this population in an environment completely devoid of this species in the recent past, provides new evidence of the current tropicalization of the Mediterranean caused by global warming.